Midnight [videorecording (DVD)] - Leisen, Mitchell, 1898-1972; Colbert, Claudette; Ameche, Don; Barrymore, John, 1882-1942 (Universal Studios Home Entertainment, 2008)
A penniless showgirl, impersonating a Hungarian countess, quickly adapts to her new lifestyle with the help of an aristocrat. But she finds herself falling in love with yet another poor man.